Evaluation and management of blunt injury abdomen based on focussed assessment with sonography in trauma - Ahmed, Sameer (International Journal of Research in Medical Sciences, 2020)
Background: The initial evaluation of patient with multiple trauma is a challenging task. FAST (focussed assessment with sonography in trauma) provides a viable alternative to computed tomography in blunt abdominal trauma patient. The aim of this study was to find the accuracy and utility of FAST in clinical decision making, as well as limitations. Methods: A total of 100 patients with blunt abdominal trauma who underwent FAST examination were included. Positive scan was defined as the presence of free intraperitoneal fluid. The sonographic scoring for operating room triage in trauma (SSORTT Score) was calculated using cumulative sum of ultrasound score, systolic blood pressure, and pulse rate. FAST findings were compared with computed tomography findings and in operated cases compared with surgical findings & clinical outcome. Results: We determined SSORTT score in all 100 cases. In our study, the sensitivity, specificity, positive and negative predictive values for FAST in identifying intraabdominal injuries were 93.9%, 94.2%, 87.5%, and 97.2%. In our study we found out that patients with a SSORTT score of 2 and above had a high likelihood of requiring a therapeutic laparotomy. Conclusions: In our study we found that FAST is a rapid, reproducible, portable and non-invasive bedside test, and can be performed at the same time as resuscitation. Ultrasound is limited mainly by its low sensitivity in directly demonstrating solid organs injuries.